Hubungan Partisipasi Dalam Pengelolaan Gabungan Kelompok Tani Dengan Status Kesehatan Hutan - M. Rizky Pratama; Rahmat Safe'i; Hari Kaskoyo; Indra Gumay Febryano1 (Fakultas Kehutanan, Universitas Hasanuddin, 2022)
: Implementation of community forest to provide access and increase the capacity of communities around forests in sustainable forest management. The purpose was to determine the relationship between participation in forest management with health of community forest clusters, which was carried out in October 2022 in the community forest of Margo Rukun and Harapan Santosa forest farmer groups, KPHL Batu Tegi, Tanggamus Regency, Lampung Province. The methodology is calculating community participation scores, calculating forest health indicators, and Spearman Rank correlation analysis. The results of this study indicate a high involvement in the process and utilization of gopoktan Margo Rukun members with a high average participation. Meanwhile, the level of involvement is high in the implementation and supervision stages of Gopotkan Harapan Sentosa, with a high level of involvement. Forest health monitoring results show that there are 4 cluster plots with the final value of forest health status in cluster plot 1 (8.75) good category, cluster plot 2 (3.49) bad category, cluster plot 3 (8.25) good category, cluster plot 4 (3.30) bad category. The results of forest health monitoring health status in community forests with an average final value is 5.95 which is included in the medium category. The relationship between the level of participation and forest health status in the Margo Rukun Gapoktan lies in the planning, implementation, and utilization stages. In contrast, the Harapan Sentosa Gapoktan lies in the implementation and utilization stages.